CONSTRAINTS IN DAIRY FARMS IN KHAMMAM DISTRICT OF TELANGANA STATE - M.H.V. BHAVE, CH. RAMYA SRI, K. SUHASINI, M. SRIKANTH REDDY and (The Journal of Research, PJTSAU, 2019)
Dairying in India, in general is closely interwoven as an integral part of agriculture and it has also been a source of livelihood of the weaker sections of rural community, especially the small and marginal farmers. In dairying a change that is taking place is shift from the non monetary inputs to monetary inputs, due to the decreasing size of land holdings and shrinking common property resources. The cost plays an important role in economic viability of a dairy enterprise. It is a critical economic indicator for milk producers, consumers and policy makers to provide an effective linkage between the milk producers and consumers for fixing the price of milk rationally. Generally, a milk producer can increase his dairy income in two ways viz., either by increasing the milk production or by reducing cost of milk production